Vegetation structure and biomass dynamics following a severe typhoon in post-disturbance mining landscapes of Cagdianao, Dinagat Islands, Philippines - Sarmiento, Roger T.; Dulawan, John Michael A.; Mercado, Joel A. (Brawijaya University, 2026)
In December 2021, a severe typhoon caused widespread damage to forest ecosystems across Northern Mindanao, including the Dinagat Islands, an ecologically significant area yet subjected to ongoing mining activities. This study presents a post-disturbance floristic and biomass assessment conducted two years later within a 226-hectare Mineral Production Sharing Agreement site in Cagdianao, Dinagat Islands, Philippines. The objective was to evaluate early forest regeneration, species diversity, and biomass dynamics in a disturbed tropical mining landscape. Vegetation was dominated by young regrowth, primarily sapling-stage trees. Using a quadrat-transect design with 10 × 10 m plots spaced at least 250 m apart, the survey documented 48 tree species from 42 genera and 28 families, with an overall Shannon–Wiener diversity index (H’) of 3.142, ranging from 0.974 to 2.424 across sampling stations. The understory vegetation comprised 69 taxa representing 40 families, indicating a heterogeneous plant community in early succession. Conservation assessments identified nine species listed on the IUCN Red List and seven categorized as threatened under DENR DAO 2017-11. Remote sensing analysis using ESA Biomass data revealed that 51.4% of the area experienced biomass loss immediately after the typhoon, resulting in a net decline of 4.28%, but partial recovery of 25.63% was observed in 2022. These findings underscore the importance of integrating floristic assessments with satellite-derived biomass monitoring to track post-disturbance ecosystem dynamics. The study contributes to evidence-based biodiversity conservation, ecological monitoring, and the development of sustainable post-mining rehabilitation strategies in typhoon-prone tropical ecosystems.